2018
DOI: 10.1364/boe.10.000322
|View full text |Cite
|
Sign up to set email alerts
|

Methods for registering and calibrating in vivo terahertz images of cutaneous burn wounds

Abstract: A method to register THz and visible images of cutaneous burn wounds and to calibrate THz image data is presented. Images of partial and full thickness burn wounds in 9 rats were collected over 435 mins. = 7.25 hours following burn induction. A two-step process was developed to reference the unknown structure of THz imaging contrast to the known structure and the features present in visible images of the injury. This process enabled the demarcation of a wound center for each THz image, independent of THz contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Based on the degree of tissue edema, some studies have reported that the use of terahertz imaging could determine the depth of burns (20)(21)(22). However, terahertz imaging cannot observe the tissue structure and the state of the microcirculation, so solely relying on the degree of edema to assess burn depth has obvious limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the degree of tissue edema, some studies have reported that the use of terahertz imaging could determine the depth of burns (20)(21)(22). However, terahertz imaging cannot observe the tissue structure and the state of the microcirculation, so solely relying on the degree of edema to assess burn depth has obvious limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have been done both ex vivo [55] and in vivo [56] on various animal models such as Sprague-Dawley rats [57] and Landrace Yorkshire cross pigs [59] whose skin have similarities with humans. Furthermore, differences in the post-burn water accumulation dynamics caused by edema have been well studied with terahertz methods [59,60]. In such studies, an initial depletion of the hydration at the burn site, in the minutes following the injury, produces a decrease of the terahertz reflection at the cutaneous surface.…”
Section: Medical Imagingmentioning
confidence: 99%
“…[Reprinted] with permission from [60] Ā©The Optical Society first in vivo measurements of skin [61] were reported in the early 2000s; however, the degree of sophistication required for actual medical applications has maintained interest in the topic up to the present day [62]. As one important example, diabetic foot syndrome, a consequence of diabetes, is a condition for which there is currently no objective diagnostic test, particularly in early stages.…”
Section: Medical Imagingmentioning
confidence: 99%
“…Terahertz time-domain spectroscopy (THz-TDS) has emerged as a noninvasive and objective tool for assessment of various biological tissue types, including determining corneal hydration [29][30][31][32] , diagnosis of brain tumors [33][34][35] , diabetic foot syndrome 36 , delineating breast cancer tumor margins [37][38][39][40][41] , and classification of burn injuries 42,43 . In burn diagnosis applications, it was shown that the reflectivity of the full-thickness burns in rodent models is higher compared to the normal skin over a frequency range between 0.2 and 1 THz 44 .…”
Section: Introductionmentioning
confidence: 99%